Effectiveness of multi-frames video recorded experiments on pre-university students achievement for capacitor topic - Ramly Rosazley, Jaafar Rosly, Mat Daud Anis Nazihah, Ali Shaharudin, Wan Mokhtar Wan Zul Adli, Haron Roszairi, Mohamed Safian Nur Azmina (Universiti Pendidikan Sultan Idris, 2016)
Effectiveness of multi-frames video recorded experiments on pre-university students achievement for capacitor topic by Ramly Rosazley, Jaafar Rosly, Mat Daud Anis Nazihah, Ali Shaharudin, Wan Mokhtar Wan Zul Adli, Haron Roszairi, Mohamed Safian Nur Azmina,